ASURANSI JIWA DALAM PERJANJIAN PENGALIHAN KREDIT PEMILIKAN RUMAH BERSUBSIDI DI BTN CABANG TANGERANG: Life Insurance in the Subsidized Mortgage Take-Over Agreement at BTN Tangerang Branch - Septianingsih, Alizanoor; Abrianti, Sharda (AMICUS CURIAE, 2025)
For further carrying its function to distributing funds into the community, Banks are trusted by the government to issue loan facility in the form of Subsidized Mortgage. The issue of this ease facility is in line with the bank’s purpose as stated in Law Number 7 of 1992 Concerning Baking and Law Number 10 of 1998 Concerning Amendments to Law Number 7 of 1992 Concerning Banking, which is to improve the welfare of the people. In this matter, aiming for the low-income salary person thus they could possess their own residence as well. The occurring problem is often the mortgage credit runs inappropriate and take-over credit has to be done, thereafter questions regarding life insurance claim in mortgage credit agreement arouse; This research is normative research, characterized by its descriptive nature and using qualitative approach in analyzing data, subsequently deductive logic is used to draw conclusions. The analysis results can then be concluded that the existence of life insurance in subsidized mortgage agreement is a clause that must be present to minimize the risks borne by the bank.